Comparing the seismic performances of shallow beam connections with accordion webs and reduced sections: An experimental study. (December 2019) - TahamouliRoudsari, Mehrzad; Moradi Garoosi, AllahReza; Alipour, Ali; Torkaman, Morteza; Moghadam Abrishami, Hossein; Rambarzini, Mehran; Doudman Koushki, Alireza; Khodaparast, Shahrokh; Bonyadirad, Shahab
Abstract: As the depth of the beam increases, the probability of the occurrence of lateral-torsional buckling and damage increases as well. Researchers have been able to resolve this problem to some extent by changing the web of the beam into an accordion web. Extensive research has been conducted on deep beams with accordion webs. However, no detailed study has been carried out regarding the performance of the accordion web in shallow beams and its comparison to Reduced Beam Section (RBS) connections. Therefore, seven full-scale experimental samples were constructed and tested under the influence of cyclic quasi-static loading. The samples included conventional end-plate connection, beam with accordion web with angles of 11 and 22°, conventional RBS connection, and RBS connection with accordion web. The results showed that all of the samples satisfy the criteria for special moment resisting frame's ductility. The RBS sample and the samples with accordion webs were the ones with respectively the highest and lowest ductilities. It therefore seems that using the accordion web in shallow beams, is not properly justified.